Environmentally Glowing: Eco-Linguistic Reading on Natural Skin Care Advertisement - Nurisma, Maulidiya Aulia; Tuqo, Fina Ainut; Azizah, Luthfiah Asih (Politeknik Harapan Bangsa Surakarta, 2024)
The growing competition in the skincare industry has prompted brands to adopt eco-friendly labeling to attract environmentally conscious consumers and promote global sustainability efforts. This study focused on how natural skincare advertisements use green advertising strategies to promote their product. This study aims to address this gap by analyzing how three skincare brands, Sukin, From This Island, and Oasea, employ eco-linguistic elements in their Instagram advertisements. The research highlights the role of social media, particularly Instagram, as a key platform for disseminating eco-friendly messages to a global audience. Using a descriptive qualitative method, the data were collected from visual and textual components, including slogans, captions, and logos. To analyze the eco-linguistics element in Sukin, From This Island, and Oasea, this research used Green Advertising Theory by Banerjee et al and Marsh and White’s theory. The findings revealed that the brands effectively have used green advertising strategies to attract consumers. The result of this research contributes to understanding how language and visuals shape consumer perceptions of environmental issues, offering insights for marketers to design campaigns that resonate with eco-conscious audiences.